Utilization of Molecular Marker to Improve Cattle Carcass Quality in Indonesia - M. Ikhsan Shiddieqy; Nurul Pratiwi; Bayu Dewantoro Putro Soewandi (Indonesian Center for Animal Research and Development, 2019)
Cattle is one of the commodities that have a national priority to achieve self-sufficiency in animal protein food for the Indonesian people. Beside beef sufficiency, demand on good quality meat in Indonesia is also increasing. Good quality carcass with lower fat content can give higher economic value. The purpose of this paper is to discuss the use of molecular markers to improve the quality of beef cattle carcass. Heritability value in carcass characteristic is low to moderate value, but it can be increased by selection using certain molecular markers. Several genes have been identified and correlated with carcass quality in several breed of cattle. Study in Bali cattle showed that the Calpain (CAPN1) and Calpastatin (CASTN) genes could be used as molecular markers to select Bali cattle with higher quality carcass because these genes were associated with carcass quality traits. In conclusion that Calpain (CAPN1) and Calpastatin (CASTN) genes can be used for local beef cattle selection toward better carcass quality and have opportunity to be utilized to improve carcass quality of other beef cattle breeds in Indonesia.